2022
DOI: 10.1016/j.semarthrit.2021.11.012
|View full text |Cite
|
Sign up to set email alerts
|

Antimalarials exert a cardioprotective effect in lupus patients: Insights from the Spanish Society of Rheumatology Lupus Register (RELESSER) analysis of factors associated with heart failure

Abstract: Background/objectives Factors associated with chronic heart failure (CHF) in patients with systemic lupus erythematosus (SLE) have received little attention. Recent data on the use of hydroxychloroquine in the treatment of SARS-CoV-2 infection have cast doubt on its cardiac safety. The factors associated with CHF, including therapy with antimalarials, were analyzed in a large multicenter SLE cohort. Methods Cross-sectional study including all patients with SLE (ACR-1997… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 29 publications
1
4
0
Order By: Relevance
“…In fact, we observed a 38% reduction in the risk of adverse cardiac events per each 1‐mg/kg increase in baseline HCQ weight‐based dose. This finding is contrary to our original hypothesis and in concordance with multiple previous studies that have shown an association of HCQ use with lower cardiovascular risk (4,5,7). This inverse association between HCQ weight‐based dose and adverse cardiac events was not observed among smokers, except for those who were taking HCQ for over 5 years.…”
Section: Discussionsupporting
confidence: 67%
See 3 more Smart Citations
“…In fact, we observed a 38% reduction in the risk of adverse cardiac events per each 1‐mg/kg increase in baseline HCQ weight‐based dose. This finding is contrary to our original hypothesis and in concordance with multiple previous studies that have shown an association of HCQ use with lower cardiovascular risk (4,5,7). This inverse association between HCQ weight‐based dose and adverse cardiac events was not observed among smokers, except for those who were taking HCQ for over 5 years.…”
Section: Discussionsupporting
confidence: 67%
“…Current knowledge of HCQ-related heart failure in SLE is mostly limited to case reports and case series (7,14,16,17). Similar to our results, a recent cross-sectional study that included 117 patients with SLE and heart failure and 3,506 SLE controls found a decreased odds of heart failure among HCQ users (OR 0.28 [95% CI 0.17-0.45], P < 0.001) (7). However, this study did not look at HCQ doses but rather compared HCQ users versus nonusers, who are inherently 2 very different populations of patients with SLE.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Thus, a meta-analysis involving patients with RA and SLE showed that using CQ/HCQ reduced the risk of cardiovascular disease in patients with rheumatic diseases (RR 0.72, 95% CI: 0.56-0.94, p = 0.013) (Liu et al, 2018) (Souza Botelho et al, 2021. Furthermore, studies after this meta-analysis have corroborated the results in patients with SLE (Lo et al, 2021b;Rúa-Figueroa et al, 2022).…”
Section: Pharmacological Treatment and Adverse Eventsmentioning
confidence: 76%